Digital transformation in volcano tourism:: A systematic review of marketing, engagement, risk, and sustainability - Mohammad Wartaka; Usep Suhud; Sumardjono Sumardjono; Dede Suparman; Dadi Muhamad Hasan Basri (Journal of Commerce, Management, and Tourism Studies, 2026)
Digital transformation increasingly shapes how tourism destinations are promoted, experienced, interpreted, and managed, yet evidence in volcano tourism remains fragmented across marketing, visitor engagement, safety, and sustainability research. This systematic literature review examined Scopus-indexed journal articles published within the 2015–2025 review period. Following PRISMA 2020, 80 records were identified and 14 studies met the final eligibility criteria. Descriptive bibliometric profiling and thematic synthesis showed that eligible publications emerged from 2020 onward and remained geographically concentrated. Three principal domains were identified: digital destination marketing and branding; technology-enabled visitor experience and interpretation; and digital safety, resilience, and visitor management. Across these domains, digital strategies contribute through four pathways: promotion and branding, interpretation and experience, safety and resilience, and responsible or sustainable tourism. The synthesis further identifies an attractiveness–risk duality, positions visitor–destination engagement as an integrative conceptual bridge, and highlights the hybrid digital–physical information environment as an important boundary condition. Sustainability emerges as a cross-cutting but insufficiently measured outcome. An integrative framework is proposed linking digital capabilities, functional domains, visitor–destination engagement, and responsible and sustainable volcano tourism. Future research should integrate the complete visitor journey, evaluate technology effectiveness, operationalize sustainability outcomes, and expand cross-destination comparisons.